STUDY OF CRYOGENIC TEMPERATURE EFFECT ON MECHANICAL ALLOYING IN MICROSTRUCTURE AND MECHANICAL PROPERTIES OF REDUCED ACTIVATION FERRITIC (RAF) OXIDE DISPERSION STRENGTHENED (ODS) : CRITICAL REVIEW - Maradewa Maksum, Arvi
Reduced Activation Ferritic (RAF) Oxide Dispersion Strengthened (ODS) is an alloy that is projected to be used as a structural material for fusion nuclear reactors as the first wall and breeding blanket. The material used for such condition, must have resistance to oxidation and high temperature creep, high temperature mechanical properties, and resistance to radiation. The RAF ODS alloy composed of low neutron activation elements (Fe, Cr, W, Ti, Si, Ta, Zr, Mn, and V), where the presence of these constituent elements plays a role in increasing resistance to harsh environment in nuclear reactors. One of the influential processes in the fabrication of RAF ODS alloys is mechanical alloying. One of the parameters that influence the alloying process is the operating temperature. It is known that low temperature mechanical alloying (-196 to -70°C) can increase brittle fractures thereby affecting the microstructure and mechanical properties of the alloy. First, assortment of information related to RAF ODS, RAF ODS strengthening mechanisms, mechanical alloying, cryomilling, and the effects of low temperature mechanical alloying on the microstructure and mechanical properties of alloys. Other supporting data were also collected to facilitate the writing process. Then discussion and analysis were conducted to answer all the objectives of this literature. The results of the discussion and analysis will lead to an understanding of the effects of cryomilling on RAF ODS alloys. From this study, conclusions and suggestions obtained from the literature review From the literature review, it is known that cryomilling increase the efficiency of reduction on powder particle size due to supression on the cold welding mechanism. In addition, cryomilled alloys have smaller grain size and (nanoclusters) NCs, as well as greater density of NCs when compared to room temperature mechanical alloying. The mechanical properties of cryomilled alloys show better yield strength and fracture toughness up to 500°C when compared to room temperature milling alloys. However, above this temperature, there is high temperature degradation caused by grain boundary weakening